KEEFEKTIFAN PEMBELAJARAN MATEMATIKA BERBASIS SMART DENGAN STRATEGI TAI PADA MATERI SEGITIGA KELAS VII - Aryo Andri Nugroho (LPPM Universitas Pekalongan, 2011)
Abstract This study is aimed to increase the students’ achievement in learning mathematics on grade VII SMP Islam Pekalongan using SMART-Based Mathematics Learning by TAI Strategy. It is a Queasy Experimental model. The population is the students of grade VII SMP Islam Pekalongan that consists of eight classes. The writer uses the random sampling to choose the samples; there are two classes, class VII 1 as the experimental class and class VII 2 as the control class. The variables are the students’ activeness (X1) and skill process (X2) as the independent variables, meanwhile the students’ achievement (Y) is as dependent variable. The methods of collecting data are by observation and learning achievement test. The data analyses are by comparison and influence test. The result of this study shows that the students’ achievement is 77,59. It means that the students’ achievement is good. There is a difference between the experimental and control class. The variables of students’ activeness and skill process have positive influences on the students’ achievement with the regression y^= -33,964 + 1,003 X1 + 0,434 X2 and the influence is as much as 39%. That shows the experimental class learning is effective. Keywords: SMART, TAI, Cooperative Learning